PEMILIHAN ATRIBUT EVALUASI KINERJA DOSEN YANG BERPENGARUH TERHADAP TINGKAT KEPUASAN MAHASISWA DALAM MENGIKUTI MATA KULIAH - , Ning Ratwastuti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The level of student satisfaction on a course is determined by many factors, one of them is lecturer performance. Evaluation of lecturerâs performance can be done by student as respondent. Course evaluation dataset from 5280 students of Gazi University was used in this research. From 28 attributes in the dataset, there were 12 attributes related to the level of student satisfaction in enrolling courses, while 16 other attributes indicated the studentsâ evaluation of lecturer performance. The aim of this research was to obtain subset containing lecturer performance attributes which had significant effect on the level of student satisfaction in enrolling courses. Clustering process was done to get class attribute that indicated the level of student satisfaction in enrolling courses. Attribute selection methods such as CFS, Wrapper, Gain Ratio, and RELIEF were used to determine the input attributes (studentsâ evaluation of lecturer performance) which had significant effect on the level of student satisfaction in enrolling courses. Classification process was used as an evaluation method, while the accuracy value, ROC, TP rate, and FP rate were used as evaluation parameter to determine the best subset. The evaluation showed that the classification using the subset attribute was better than the classification using all attributes. Subset from Wrapper Attribute Selection was the best subset made in this research, generating 88.02% accuracy, 0.928 ROC, 0.880 TP rate, and 0.079 FP rate. There were 7 attributes that significantly affect on the level of student satisfaction in enrolling courses, such as: lecturer's knowledge was relevant and up to date, lecturer taught in accordance with the announced lesson plan, lecturer was committed to the course and was understandable, lecturer arrived on time for classes, lecturer was open and respectful to studentâs view about the course, lecturer gave relevant homework, assignments/projects, and helped/guided students, and lecturer responded to questions about the course inside and outside of the course